Consecutive days of prolonged tennis matchplay affect physiological, performance, and perceptual responses - Gescheit, D. T.; Cormack, S. J.; Reid, M.; Duffield, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: To determine the performance, physiological, and perceptual responses to consecutive days of prolonged tennis matchplay. Methods: Seven well-trained male tennis players completed 4 h competitive tennis matches on 4 consecutive days. Pre- and post-match measures included tennis (serve speed and accuracy), physical (20m sprint, countermovement jump, shoulder rotation maximal voluntary contraction, isometric mid-thigh pull), perceptual (Training Distress Scale (Main and Grove, 2009), soreness), and physiological (body mass, Creatine Kinase, Testosterone, Cortisol) variables. Activity profile was assessed by heart rate, and three-dimensional load (sum of the mediolateral, anteroposterior, and vertical vertor loads), while Rating of Perceived Exertion (RPE) was collected every 30 minutes. Statistical analysis compared within and between day values. Changes (± 90 % confidence interval (CI)) equal to or greater than 75% likely to exceed the smallest important value were considered practically important. Results: Three-dimensional load (mean reduction ± SD; 1064.8 ± 83.6) and effective playing time reduced on days 2-4 compared to day 1 (28 ± 3 %). Total strokes hit and RPE did not change. Post-match 20 m sprint (mean percentage change ± 90% CI; 3.0 ± 3.7%) and countermovement jump (-15.6 ± 15.4%) performance declined on days 2-4 compared to pre-match day 1. Although serve velocity was maintained, compromised post-match serve accuracy was evident (days 2: 23.6 ± 32.0% and 3: 20.4 ± 17.8% as compared to pre-match day 1). Cortisol declined and Creatine Kinase increased on all days, whereas changes in Testosterone were more variable. Conclusions: Four-hours of matchplay over 4 consecutive days realised declines in total movement, which may have been impacted by changes in tactical approach. Increases in perceptual and biochemical markers of muscle damage, decrements to sprinting and jumping ability, and reduced mood states, also highlight probable neuromuscular and perceptual fatigue.